Pendampingan Aplikasi Sistem Pembayaran Digital (QRIS) Sebagai Upaya Peningkatan Daya Saing pada UMKM Sektor Jasa di Samarinda - Dwi Martiyanti; Henny Febrianti; Tatasya Nur Fadhilah; Nikolaus Cholin Huvat; Dina Rosyadah; Risma Ayu Nur Aisyah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service activity aims to improve the skills of Salon Yudi's MSME partners in using the QRIS digital payment system application in an effort to increase business competitiveness in the digital era. The method of implementing this service uses socialization and mentoring. The target of this activity is to increase the competitiveness of MSMEs through non-cash transaction processing services so that they run quickly and efficiently. The evaluation instrument for this activity uses an interview sheet and is analyzed descriptively. The results of this service show that Salon Yudi partners have the knowledge and skills to apply the QRIS digital payment system to their customers. This positive impact is shown by the faster payment processing time for customers, making it more efficient and fulfilling the need for customers to use the payment process, which is currently non-cash.